From Epidemiologic Knowledge to Improved Health: A Vision for Translational Epidemiology. Issue 12 (30th March 2019) - Windle, Michael; Lee, Hojoon D; Cherng, Sarah T; Lesko, Catherine R; Hanrahan, Colleen; Jackson, John W; McAdams-DeMarco, Mara; Ehrhardt, Stephan; Baral, Stefan D; D'Souza, Gypsyamber; Dowdy, David W
Abstract: Epidemiology should aim to improve population health; however, no consensus exists regarding the activities and skills that should be prioritized to achieve this goal. We performed a scoping review of articles addressing the translation of epidemiologic knowledge into improved population health outcomes. We identified 5 themes in the translational epidemiology literature: foundations of epidemiologic thinking, evidence-based public health or medicine, epidemiologic education, implementation science, and community-engaged research (including literature on community-based participatory research). We then identified 5 priority areas for advancing translational epidemiology: 1) scientific engagement with public health; 2) public health communication; 3) epidemiologic education; 4) epidemiology and implementation; and 5) community involvement. Using these priority areas as a starting point, we developed a conceptual framework of translational epidemiology that emphasizes interconnectedness and feedback among epidemiology, foundational science, and public health stakeholders. We also identified 2–5 representative principles in each priority area that could serve as the basis for advancing a vision of translational epidemiology. We believe an emphasis on translational epidemiology can help the broader field to increase the efficiency of translating epidemiologic knowledge into improved health outcomes and to achieve its goal of improving population health.